The Preferences of the Indonesian Young Enterpreneurs Association (HIPMI) at the State Islamic University of North Sumatera towards Enterpreneurial Interest - Muhammad Ilzam Harahap; Muhammad Lathief Ilhamy Nasution; Juliana Nasution (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study aims to analyze the preferences of the Indonesian Young Entrepreneurs Association (HIPMI) at the State Islamic University of North Sumatra (UINSU) regarding entrepreneurial interest. A mixed-methods approach was employed, combining quantitative and qualitative methodologies. Data were collected through questionnaires distributed to 61 active members of HIPMI UINSU and interviews with selected participants. A total of 30 samples were analyzed using SPSS Version 23 with path analysis. The findings reveal that understanding has no significant effect on entrepreneurial interest, as indicated by a t-value of 0.604 (p = 0.551). Similarly, religiosity does not significantly influence entrepreneurial interest, with a t-value of 0.239 (p = 0.813). In contrast, motivation positively and significantly impacts entrepreneurial interest, as shown by a t-value of 3.322 (p = 0.003). The combined analysis through ANOVA indicates that understanding, religiosity, and motivation collectively have a positive and significant effect on entrepreneurial interest. These results align with the Theory of Planned Behavior (TPB), which highlights the role of positive attitudes, subjective norms, and perceived behavioral control in shaping entrepreneurial intentions. This study underscores motivation as a key driver of entrepreneurial interest among HIPMI UINSU members.